Analisis Yuridis Aset Kripto Sebagai Objek Gadai Di Indonesia - Putra, Zullfikri Ensa; Wicaksono, Setiawan; Suwardiyati, Rumi (Faculty of Law, Universitas Brawijaya, 2024)
This research aims to analyze the regulation of Crypto Assets as collateral in Indonesia, as well as examine whether Crypto Assets meet the characteristics as collateral objects according to KUHPerdata, KUHD, and POJK No. 31/POJK/05/2016 concerning Pawnshop Business Jo SE OJK No. 52/SEOJK.05/2017 regarding the Implementation of Conventional Pawnshop Business Activities. This study employs a normative juridical method with statute approach and conceptual approach. Legal materials will be analyzed using descriptive analytical techniques. The author found that Crypto Assets have gained legal recognition as a commodity asset with the issuance of Minister of Trade Regulation No. 99 of 2018. However, positive law in Indonesia still does not provide legal certainty regarding Crypto Assets as collateral. Crypto Assets can be categorized as intangible movable property according to KUHPerdata and KUHD. Crypto Assets also have economic value as they can be assessed or valued in terms of money. The author recommends that the government update SE OJK No. 52/SEOJK.05/2017 to include Crypto Assets as one of the collateral objects in Indonesia.